Impact des coopératives féminines sur la préservation et la valorisation de l’arganeraie : cas de la coopérative Tafyoucht (confédération des Ait Baamrane, Anti-Atlas, Maroc) - Hassan Faouzi (Confins)
The Argan tree (Argania spinosa) is a tree that grows mainly in Morocco. Argan trees cover approximately 800,000 hectares in the south-west of Morocco. In these arid and semi-arid areas, 1.3 million people are involved on the exploitation of traditional agroforestry systems based on the Argan tree. The area of the Argan tree gets deteriorated year by year due to the combined effect of population growth and overgrazing. In less than a century, more than one third of the forest has disappeared. In the last fifteen years, efforts have been made to define the conditions of a really sustainable development. Argan oil, is undoubtedly the production on which could be based a socio-economic development project. The involved population and local authorities have become aware of the magnitude of this problem, which represents the development of the Argan tree, its sociocultural and economic value and the need to act. This is reflected on the creation of cooperatives that bring together the improvement of oil extraction and its commercialization to benefit women and the preservation of this resource as well as the fight against desertification.